2018
DOI: 10.18203/2320-1770.ijrcog20182860
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with episiotomy practice in Bukavu, Democratic Republic of the Congo

Abstract: Background: The primary objective of the present study is to determine the episiotomy rate and factors associated with practice of episiotomy at the maternities in Bukavu town, South-Kivu, DRC.Methods: A case-control study was carried out the women who underwent the episiotomy (case) and those which did not undergo episiotomy (control) over one 12 months period between January to December 2015. A total of 1878 women had a vaginal delivery at a rate of one case for one control (939 cases and 939 controls) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 0 publications
1
9
2
Order By: Relevance
“…Whereas, this finding was almost two to three times higher than the study conducted in the Democratic Republic of Congo 20.4%, 40 Brazil 29.1%, 41 Vietnam 29.9%, 42 Burkina Faso 22%, 43 and Nigeria 9.3%. 44 The reason for this might be that in those countries the practice of routine episiotomy was restricted by national guidelines and they were valuing recommendations from WHO.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Whereas, this finding was almost two to three times higher than the study conducted in the Democratic Republic of Congo 20.4%, 40 Brazil 29.1%, 41 Vietnam 29.9%, 42 Burkina Faso 22%, 43 and Nigeria 9.3%. 44 The reason for this might be that in those countries the practice of routine episiotomy was restricted by national guidelines and they were valuing recommendations from WHO.…”
Section: Discussioncontrasting
confidence: 58%
“…There are some studies from different countries that support this finding; Iran, 38 Colombia, 50 Vietnam, 42 and Congo. 40 This might be because women with first pregnancy have tight perineum which increases the risk of perineal injury and the obstetrics care providers might have a belief of episiotomy necessity for primigravid women even without clear indications.…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen primary studies employed an analytical cross-sectional study design, while the remaining three studies employed a descriptive cross-sectional study design. Regarding the settings in which the studies were conducted eight studies were conducted in Ethiopia ( 45 , 46 , 54 , 57 , 61 , 64 , 66 ), eight in Nigeria ( 40 – 42 , 58 , 63 , 65 , 82 ), and the remainder of the studies were conducted in the Democratic Republic of the Congo (DRC) ( 69 ), Zimbabwe ( 83 ), Uganda ( 55 ), Ghana ( 84 ), and Burkina Faso ( 85 ). The majority of the studies, 16 (76.2%), were reported from Eastern and Western African countries.…”
Section: Resultsmentioning
confidence: 99%
“…According to Macleod et al ( 50 ), Koskas et al ( 51 ), Giannella et al ( 52 ), Cromi et al ( 48 ), Beyene et al ( 53 ), Tobiaw Tefera et al ( 54 ), Teshome et al ( 46 ), and Pebolo et al ( 55 ) episiotomy was significantly associated with a prolonged second stage of labor. Furthermore, macrosomia ( 42 , 51 , 53 , 54 , 56 – 58 ), advanced gestational age ( 49 , 59 , 60 ), breech presentation ( 50 , 51 , 57 , 60 – 62 ), primiparity ( 40 – 42 , 45 , 46 , 53 , 56 – 58 , 61 , 63 – 65 ), oxytocin use ( 45 , 53 , 59 , 62 , 66 , 67 ), meconium-stained amniotic fluid ( 49 , 50 ), reduced apgar score ( 67 ), assisted breech vaginal delivery or vaginal operative delivery (forceps) ( 41 , 42 , 53 , 54 , 56 , 58 , 61 , 63 , 66 ), analgesia ( 49 , 67 , 68 ), non-reassuring fetal heart rate pattern ( 68 ), persistent occipito posterior position ( 41 ), post-term pregnancy ( 45 ), fetal distress ( 47 , 69 ), perineal tear ( 66 ), private character of the mother ( 41 ), a history of gestational hypertension ( 45 ), birth spacing <2 years ( 66 ), vaginal birth after cesarean section ( …”
Section: Introductionmentioning
confidence: 99%
“…Findings in Israel, Kurdistan region, Republic of Congo, Zimbabwe and in our country at Mizan Aman general Hospital, at Akaki Kality and at Saint Paul’s hospital Millennium Medical College showed that perineal laceration (tear), duration of second stage of labour more than 90 min, ANC follow up history, time of delivery, previous history of episiotomy and known medical diseases were significant predictors for episiotomy practice [ 43 , 44 , 46 , 47 , 49 , 52 ]. Studies in Northeast of Iran, Brazil, Republic of Congo, Israel, Kurdistan region, Zimbabwe and in our country at Mizan Aman general Hospital, at Akaki Kality, at Saint Paul’s hospital Millennium Medical College, at Axum town public health institution and at Jima teaching Hospital identified that birth weight of 4 kg and above, gestational age, presence of meconium, sex the neonate, breech and shoulder presentation and condition of fetal heart rate were significant factors for episiotomy practice [ 33 , 37 – 39 , 41 , 43 – 55 ].…”
Section: Introductionmentioning
confidence: 94%